Welfare and Party Politics in Latin America - Pribble, Jennifer (Cambridge University Press, 2013)
Systems of social protection can provide crucial assistance to the poorest and most vulnerable groups in society, but not all systems are created equally. In Latin America, social policies have historically exhibited large gaps in coverage and high levels of inequality in benefit size. Since the late 1990s, countries in this region have begun to grapple with these challenges, enacting a series of reforms to healthcare, social assistance and education policy. While some of these initiatives have moved in a universal direction, others have maintained existing segmentation or moved in a regressive direction. Welfare and Party Politics in Latin America explores this variation in Argentina, Chile, Uruguay and Venezuela, finding that the design of previous policies, the intensity of electoral competition, and the character of political parties all influence the nature of contemporary social policy reform in Latin America.